Tne Influence of Learning Management Systems (LMS) and the Value of Istiqamah Attitude on the Quality of Education - Ansori, Aan; Tarihoran, Naf’an; Nugraha, Enung (International Journal of Education, Teaching, and Social Sciences, 2024)
This study investigates the influence of the Learning Management System (LMS) and the Value of Istiqamah Attitude on the Quality of Education at Sultan Maulana Hasanuddin State Islamic University, Banten. This research is motivated by a profound need to understand the factors that can affect and enhance the quality of education. The research method uses a quantitative approach by collecting data through surveys of students at UIN SMH Banten. Regression analysis techniques are used to test the research hypotheses. The main findings of this study are that the Learning Management System and the Value of Istiqamah Attitude positively influence the Quality of Education at UIN SMH Banten. The results of the analysis conclude that effective coordination in the implementation of LMS and the values of istiqamah can improve the quality of education. The partial influence of LMS on the quality of education is significant, with a T-statistic value of 3.526, indicating that the T-statistic value for LMS is greater than 1.96. The Value of Istiqamah Attitude also influences the quality of education, with a T-statistic value of 5.665, indicating that the T-statistic value for the Value of Istiqamah Attitude is greater than 1.96. Furthermore, LMS and the Value of Istiqamah  Attitude strongly influence the quality of education, with an effect size of 0.793 or 79.3%, which falls into the strong category. These findings provide important references for relevant stakeholders in developing strategies and policies focused on improving the quality of education. This research significantly contributes to the educational policy-making at UIN SMH Banten to improve the quality of education and provides a basis for policy and practice improvements. The implications of these findings can also assist similar institutions in their efforts to raise educational standards and produce graduates who are both high-quality and embody Islamic values in facing global dynamics.